Exploring Transition Challenges to Higher Education and Self-Directed Learning in New Students: A Mixed-Methods Approach - Indah Sari; Sipa; Miftahul Haera; Muhammad Zaky Dhiyaul Haq; Muhammad Thoriq Alfaiza (Didaktika: Jurnal Kependidikan, 2026)
The transition from secondary education to higher education often confronts first year students with intensified academic demands, with academic writing emerging as a core challenge that requires sustained regulation across planning, drafting, and revision. This study aimed to examine the relationship between self-directed learning (SDL) and academic writing competence among new students, while also exploring the dominant transition-related writing challenges and the adaptation strategies students use to cope with them. An explanatory sequential mixed-methods design was applied. In the quantitative phase, 50 first year students from the Islamic Religious Education programme at Universitas Pendidikan Indonesia (academic year 2024/2025) were selected through stratified random sampling and completed a transition challenges scale (15 items; Cronbach’s alpha = 0.87) and an adapted SDL readiness scale contextualised to academic writing (Cronbach’s alpha = 0.83), followed by a standardised academic writing task assessed using an analytic rubric. Pearson correlation showed a significant moderate positive association between SDL and academic writing competence (r = 0.387, p = 0.006, 95% CI [0.122, 0.601]), indicating that approximately 15% of variance in writing competence was associated with SDL (r² = 0.150), whereas perceived academic writing challenges were not significantly associated with writing competence (r = 0.110, p = 0.446). In the qualitative phase, semi-structured interviews with five purposively selected students from the bottom quartile of SDL scores and without prior academic writing experience were analysed thematically, yielding three themes: SDL deficits (knowledge gaps, weak planning, procrastination), academic writing challenges (idea organisation, argument development, low confidence, limited instructional clarity), and adaptation strategies (digital self-learning, peer help-seeking, workshops, and time management). Overall, the integrated findings suggest that SDL supports academic writing competence through process-level regulation and strategic support-seeking, while perceived challenges may be broadly shared among first year students and therefore do not necessarily differentiate writing performance.